KINERJA PERAWAT DI RSD Dr. H.MOH ANWAR SUMENEP MADURA DITINJAU DARI MOTIVASI KERJA - Sujono Riyadi (Wiraraja Medika : Jurnal Kesehatan, 2016)
The aim of this study was to know the relationship between job motivation with nurses performance in Dr. H. Moh. Anwar hospital Sumenep Madura. This study used survey methods  with cross sectional design. The sample of this study  consisted 110 nurses working in Dr. H. Moh. Anwar hospital Sumenep Madura. Questionnaires were self administered by respondents. Check lists were completed by the researcher. Data were analyzed using correlation kendall - tau.The results were that motivation is not associated with nurses performance (p= 0.114). The finding of this study would be recommended for the policy making in increasing of high performance climate. Key Words: Job Motivation, performance Nurse